The knowledge of basic genetic terms and available terminology in the South African Sotho languages - Mpe, Matshela (Department of Clinical Laboratory Sciences, 2024)
The use of indigenous terms during a genetic counselling session has the potential to foster a better understanding between a genetic counsellor and patient. However, it is unknown if there are specific terms for commonly used English genetic terminology in the South African indigenous languages. Furthermore, the genetic terms, knowledge and understanding of basic genetic concepts in the indigenous populations is not well-documented in the South African population. This study aimed to investigate the knowledge and understanding of basic genetic terms in the indigenous South African Sotho-Pedi-Tswana ethnolinguistic group and to explore the available common terms, sayings, and expressions. This study employed a sociolinguistic qualitative descriptive research design to investigate the study aim. Data was collected using interviews through three focus group discussions. The total number of participants was 16 Sesotho language group speakers comprising of 3 males and 13 females from a mixture of both rural and suburban areas. All participants were enrolled as students at University of Cape Town in non-health science and non-science faculties. Content analysis was used to extract the available terms and phrases used to describe genetics and inheritance concepts. Thematic content analysis was used to analyse the data from the verbatim transcripts according to three main categories: (1) terms and concepts, (2) understanding of genetic terms and (3) terminology usage. The findings reveal that there are terms and expressions available for commonly used genetic concepts and conditions commonly seen in genetic counselling. These include terminology for genetic conditions such as albinism and concepts such as inheritance and consanguinity. Participants highlighted how and when specific terms are used in their home languages and which terms were found to be offensive. Contrary to English, the Sotho-Pedi-Tswana language, like other indigenous South African languages, use more descriptive language to describe concepts. In conclusion, this study has shown that there are genetic terms or phrases that are used for common English genetic terminology in the Sotho language group. Furthermore, there is a basic understanding of genetics within their communities which genetic counsellors can use as a basis when counselling. Common genetic terminology in South African indigenous languages can be included in genetic counselling sessions to reduce communication barriers, increase rapport and minimize the need for a translator while maintaining multicultural sensitivity.